1999
DOI: 10.1016/s0008-6363(99)00093-0
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol stimulates expression of endothelial and inducible NO synthase in rat myocardium in-vitro and in-vivo

Abstract: Taken together, these results show that E2 stimulates the expression of iNOS/eNOS in neonatal and adult cardiomyocytes in-vivo and in-vitro. These novel findings provide a potential mechanism of how estrogen may modulate NOS expression and NO formation in the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
90
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(101 citation statements)
references
References 32 publications
10
90
1
Order By: Relevance
“…It also has been well demonstrated that E2 increases activity of NOS and NO release during ischemia and reperfusion (20,39,41). Furthermore, there is good evidence that the NO donor sodium nitroprusside, as well as 8-bromoguanosine 3Ј,5Ј-cyclic monophosphate (8-BrcGMP), inhibit pH i recovery in cardiac myocytes from male rats after NH 4 Cl washout in HEPES medium (22).…”
Section: Discussionmentioning
confidence: 99%
“…It also has been well demonstrated that E2 increases activity of NOS and NO release during ischemia and reperfusion (20,39,41). Furthermore, there is good evidence that the NO donor sodium nitroprusside, as well as 8-bromoguanosine 3Ј,5Ј-cyclic monophosphate (8-BrcGMP), inhibit pH i recovery in cardiac myocytes from male rats after NH 4 Cl washout in HEPES medium (22).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous estrogen protects against atherosclerosis by modulating low-density lipoprotein oxidation, binding free radicals and lowering plasma cholesterol (6,7). Enhanced expression of endothelial nitric oxide synthase and its inducible isoform in the myocardium have also been observed with the administration of exogenous estrogen (8,9).…”
Section: Introductionmentioning
confidence: 94%
“…24 These transcription factors can activate downstream target genes such as the endothelial/inducible isoforms of NO synthase as well as connexin 43 in the heart. 25,26 In the present study, we used an in vivo, closed-chest mouse model to test the hypothesis that ER␣ and ER␤ per se influence ventricular repolarization and ventricular automaticity in a female mouse model with chronic anterior MI and studied the expression of potassium channels as molecular targets of ER␣ and ER␤ underlying these differences.…”
mentioning
confidence: 99%